Lifecourse research in cancer: context, challenges, and opportunities when exploring exposures in early life and cancer risk in adulthood [version 3; peer review: 2 approved, 1 approved with reservations] - Ken Ong; Helen Croker; Ellen Kampman; Jennifer L. Baker; Trudy Voortman; Vanessa L.Z Gordon-Dseagu; Zdenko Herceg; Doris Chan; Teresa Norat; Sian Robinson (Health Open Research)
As the global population ages, and rates of modifiable risk factors for cancer change, cancer incidence and mortality continue to increase. While we understand many modifiable risk factors related to diet, nutrition, bodyweight, and physical activity in adulthood that influence cancer risk, how exposure during childhood, adolescence, and young adulthood impacts cancer risk is less clear. This is partly because the timeline from initial mutation to cancer development and diagnosis can span several decades. This long latency period creates methodological, ethical, and financial issues; as well as resource and feasibility challenges in the design, implementation, and data analysis of lifecourse studies. As such, the large majority of lifecourse studies are observational, often using recall data which has inherent bias issues. Concurrently, a new research era has begun, with mature birth cohort studies that are phenotyped/genotyped and can support studies on adult cancer risk. Several studies and consortia contain information spanning the lifecourse. These resources can support association, mechanistic and epigenetic investigations into the influences of multi-disciplinary (e.g. genetic, behavioural, environmental) factors, across the lifecourse and critical time periods. Ultimately, we will be able to produce high-quality evidence and identify how/when early life risk factors impact cancer development and survival.